Microbial and chemical hazard identification in infant food chains - KahYen Claire Yeak; Philippe Palmont; Gilles Rivière; Nawel Bemrah; Heidy M.W. den Besten; Marcel H. Zwietering (Elsevier, 2022)
To ensure foods are safe, food companies, food safety authorities, and governmental agencies work together to improve the control and prevent unwanted food contamination by either biological, chemical or physical agents, namely the hazards. Foodborne illnesses leading to diseases in humans are still frequently reported. To better protect infants and children from foodborne diseases, the SAFFI (Safe Food for Infant) project promoted by the European Union in collaboration with China, will develop an integrative approach to identify, assess, detect and mitigate risks associated with microbial hazards (MHs) and chemical hazards (CHs) in infant foods.The first stage to tackle this issue was to identify relevant hazards in infant foods. By collecting data from the literature, scientific reports, existing databases, and clinical studies and using these data to compile a list of relevant foodborne hazards. These hazards caused major foodborne outbreaks, frequently contaminated foods, have large public health impacts, and/or are dangerous to young children.After the initial identification of MHs and CHs in infant foods, we will prioritize the most relevant MHs or CHs present in specific food products and rank the risks associated with these hazards based on the probability of occurrence and severity of each hazard. Standardized and systematic hazard identification (HI) and risk ranking (RR) procedures will be developed and incorporated into HI and RR computational decision support tools that will serve to help food safety agencies, food companies, and risk assessors to identify and rank MHs and CHs in the entire infant food chain in Europe and China.